Polish Realities : New Art from Poland. - Third Eye Centre, Glasgow (Glasgow : Third Eye Centre, 1988)
Balka, Miroslaw ; Beller, Anna ; Ciecierski, Tomasz ; Dwurnik, Edward ; Klipsa, Kolo ; Korolkiewicz, Lukasz ; Kruk, Mariusz ; Kurka, Piotr ; Luczak, Hanna ; Modzelewski, Jaroslaw ; Pawlak, Wlodzimierz ; Szewczyk, Andrzej ; Tarasewicz, Leon ; etc.
Polish Realities : New Art from Poland, Third Eye Centre, Glasgow, 4th November - 3rd December 1988
boek